PENGARUH KEADILAN ORGANISASI, SISTEM PENGENDALIAN INTERN DAN KOMITMEN ORGANISASI TERHADAP KECURANGAN (FRAUD) (Studi Empiris Pada Kantor Cabang Utama Bank Syariah di Kota Pekanbaru) - Anisya Yuliana; Raja Adri Satriawan S.; Eka Hariyani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
The purpose of this reseach is to find out the influance of organizational justice on fraud, the influance of internal control system on fraud, and the influance of organization’s commitment on fraud. The population in this study are employees at the main branch office of Syariah Bank in Pekanbaru City. The data used in this study in the form of primary data. Data collection techniques with survey techniques by distributing questionnaires to the employees who work at the main branch office of Syariah Bank in Pekanbaru City. Sample selection by simple random sampling technik. Total sample are 70, the sample was calculated using Slovin formula. The method of data analysis used to test the hypothesis is multiple regression analysis using the program SPSS 20 version. The results of this study is showed that organizational justice influance on fraud, internal control system influance on fraud, and organization’s commitment influance on fraud. All of the independent variables jointly influence dependent variables which F count > F table that is 39.079 > 2.744.Keywords: Justice, Organizational, Control, Commitment and Fraud